The Usage of Gadget in School Environment: Islamic Education Teachers' Efforts in Maximizing The Usage of Mobile Phones and Their Impact Toward Students - Muhamad Rudi Wijaya; Feri Sandriya (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2019)
In today's modern era, there are many challenges that affect the success of educational goals, one of which is technology. technology is not a foreign object in the world of education and the world of students and is very influential in everyday life. One of the technologies that is growing rapidly now is electronic media. One of the electronic media that we often encounter is television, computers, mobile phones, radios and photocopiers. All media are created to be useful for the community about information and facilitate human activities. The type of research used is field research. The approach used is a qualitative approach that aims to explore deeply and describe the findings data. Therefore, it can be concluded that the efforts of PAI teachers have succeeded in maximizing the use of gadgets in students, among the efforts of which the teacher prohibits students from using gadgets during learning hours except during discussions, and provides a good example of using gadgets in students. The impact of using gadgets to students is to facilitate communication between students, increase knowledge and information, students become more creative and innovative in finding subject matter and adding friends